Alternative fuel additives from glycerol by etherification with isobutene: Structure–performance relationships in solid catalysts - Bozkurt, Özge D.; Tunç, F. Meliz; Bağlar, Nur; Çelebi, Serdar; Günbaş, İ. Doğan; Uzun, Alper (Fuel processing technology, 2015)
The expansion of biodiesel industry is expected to introduce over three million tons of glycerol into the market in 2020. Various routes have been proposed to produce glycerol-based value-added products to sustain renewable glycerol and biodiesel industries. One of these routes is the catalytic etherification of glycerol with isobutene for producing fuel oxygenate glycerol ethers as an alternative to today's petroleum based oxygenates. The products of the etherification of glycerol with isobutene are mono-, di-, and tri-tertiary butyl ethers of glycerol (MTBG, DTBG, and TTBG) and dimers of isobutene (DIB). Among these, DTBG and TTBG are the desired products for fuel blends because of their better blending properties. Different heterogeneous catalysts including acidic ion exchange resins (e.g. Amberlyst 15 and 36), sulfonated wide pore zeolites (e.g. zeolite Beta and Y), sulfonated mesoporous silica (e.g. MCM-41 and SBA-15) and some functionalized porous materials (e.g. sulfonated peanut shell, sulfonated aerogel, sulfonated graphene, spherical silica supported Hyflon) have been proved to demonstrate superior catalytic activity with complete glycerol conversion and over 90mol% selectivity to the desired ethers. Here, we review the studies on glycerol etherification with isobutene from 1990s to the first half of 2015 specifically focusing on structure–performance relationships in heterogeneous catalysts. [Display omitted] •Literature on glycerol etherification with isobutene is reviewed.•Structure–performance relationships in solid catalysts are discussed.•Parameters controlling product selectivity and catalytic activity are elaborated.•Suggestions on future research subjects are provided.